Course‐based undergraduate research to advance environmental education, science, and resource management. Issue 7 (31st May 2022) - Messager, Mathis L; Comte, Lise; Couto, Thiago BA; Koontz, Elliot D; Kuehne, Lauren M; Rogosch, Jane S; Stiling, Rebekah R; Olden, Julian D
Abstract : Every year, field excursions engage students of ecology in experiential learning that results in wide‐ranging and well‐documented pedagogical benefits. Much less appreciated, however, is the potential for these excursions to contribute long‐term data that advance scientific knowledge and natural resource management. Here we explore this potential by providing a global synthesis of field data collection, mapping the geography, temporal extent, and type of data collected by students worldwide, and calling attention to the associated benefits and challenges for course instructors. We then offer perspectives on how undergraduate courses in ecology can more broadly contribute to science, management, and policy. Finally, we highlight how several aspects – namely, existing frameworks, resources, and networks; enhanced institutional support; and synergies with the broader science community – can help undergraduate ecology courses achieve their full potential for contributing to both education and science for society.